ANSYS FLUENT-based modeling and hydrodynamic analysis for a spherical underwater robot - Chunfeng Yue; Shuxiang Guo; Maoxun Li (2013 IEEE International Conference on Mechatronics and Automation, 2013)
For an underwater robot, hydrodynamic characteristics are very important. This paper focuses on the research of the hydrodynamic analysis of a spherical underwater robot with three motions, horizontal motion, vertical motion and yaw motion. Firstly, the prototype of related second generation spherical underwater robot (SUR-II) was developed. In order to analyze the hydrodynamic characteristics of the spherical underwater robot exactly, CATIA software was employed to establish the 3D models of the flow field. For the complex structure of the developed underwater robot causing the limitations on meshing and hydrodynamic analysis, we simplified the 3D models properly. Finally, we used ANASYS FLUENT to analyze the three models and compare the simulation results to the theoretical values. It showed that the error was less than 3%. The pressure contours and velocity vectors showed the detail of the flow field when the robot implemented the basic motions.